Experimental Investigation on the Effects of Vapor Injection on Defrosting Performance Improvement of Quasi-two Stage Compression Air-source Heat Pumps - Wei Wenzhe; Xu Lintong; Liu Xuchen; Ni Long; Song Yiping; Wu Lintao (Zhileng xuebao)
During reverse-cycle defrosting of an air-source heat pump, the defrosting time is always long owing to insufficient heat sources. For the quasi-two stage compression air-source heat pump (QTASHP), owing to its larger outdoor coil operated at lower ambient temperatures, a considerable amount of heat is dissipated from the surface of the outdoor coil during defrosting, such that the long defrosting time problem becomes more severe. To improve the defrosting performance of the QTASHP, defrosting with vapor injection was proposed based on the existing cycle structure. Five groups of experiments were designed to investigate the defrosting performance. The results showed that vapor injection was beneficial for shortening the defrosting duration, decreasing power consumption, and increasing defrosting efficiency. At the optimal opening of the injection electronic expansion valve, the defrosting duration was shortened by 20.61%; the heat absorbed from water and power consumption decreased by 8.74% and 17.98%, respectively; whereas the defrosting efficiency increased by 6.22%.